Effect of cinnamon supplementation on the gut environment and ESR gene expression in the ovaries of laying quail - Bastos, Marisa Silva; Santana, Thaís Pacheco; de Oliveira Júnior, Gregório Murilo; Barbosa, Leandro Teixeira; Khatlab, Angélica de Souza; Lopes, Cláudia da Costa; Gasparino, Eliane; Del Vesco, Ana Paula (Archives of Veterinary Science, 2023)
This study aimed to analyze the effects of adding cinnamon powder to the diet on the expression of genes related to the antioxidant defense system in the intestine, the expression of alpha estrogen receptor (ESRα) gene in the ovary, and the intestinal histomorphometry in laying quails. We used 144 quails distributed in a completely randomized design with two treatments: without cinnamon supplementation (NSC) and the supplementation of 9 g/kg of cinnamon powder (CPS) added to the diet for 84 days. At the end of the experimental period, animals were sacrificed and the ovarian and duodenal tissues were collected for the expression analysis of the tumor necrosis factor alpha (TNFα), glutathione peroxidase 7 (GPX7), catalase (CAT), superoxide dismutase (SOD), and estrogen receptor alfa (ESRα) genes. Fragments of the central portions of the duodenum and jejunum were also collected for intestinal histological analysis. It was observed that quails fed with CPS diet had greater expression of the ESRα gene (P = 0.0004) than the ones from NCS diet. The animals from the CPS treatment also presented a higher height of villi (P = 0.004) and greater depth of crypts (P = 0.013) in the duodenum, and a higher height of villi and villus:crypt ratio (P = 0.005) in the jejunum. This can improve the efficiency of nutrient absorption in the intestine, resulting in a better productive performance of the birds in the phase of posture.